Correction to: Everybody wins? Chinese perceptions on Europe‑China third‑party market cooperation in Africa. - Yun, He; Zhiqin, Shi; Lida, Feng; Qiyan, Yu; Haohan, Chi (Asia Europe Journal, 2024)
This correction notice is for an article titled "Everybody wins? Chinese perceptions on Europe-China third-party market cooperation in Africa" published in the Asia Europe Journal. The authors apologize for not declaring the funding they received during the editing of their article. The research was funded by the Humanities and Social Sciences General Research Program of the Ministry of Education in China. The original article has been corrected. The publisher, Springer Nature, remains neutral regarding jurisdictional claims and institutional affiliations.